PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT(NUMBERED HEADS TOGETHER) UNTUK ENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS VII MTs DATUK BATU HAMPAR BAGANSIAPIAPI TAHUN PELAJARAN 2015/ 2016 - Suriana '; Darmadi '; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research done in class VII MTs Datuk Batu Hampar Bagansiapiapi Academic Year 2015/2016 to increased study output of student using the appliction of cooperative learning type NHT (Numbered Head Together). The research is a Class Action Research (CAR) thes force two cycle including planning, action, observation dan refletion. Techniques of collecting data used were a whritten test and an observation. Parameter research is study output of student (cognition aspect (absorption and mastery learning student), affective aspect, psychomotor aspect (simulate test) and teacher activity. Cognition aspect seen by daily quiz on first cycle is 73,21% (decent) increased on the second cycle up to 80,65% (good). Mastery learning student on first cycle are 14 students (73,68%) and increased on second cycle up to 19 students (95%). Average affective aspect on first cycle is 77,20% (good) and and increased on second cycle up to 91,88% (excellent). Average psychomotor aspect (simulate test) on first cycle is 81,97% (good) and increased on second cycle up to 95,47% (excellent). Average teacher activity in learning action on first cycle is 76,67% (good) and increased on second cycle up to 94,14% (excellent). From the result of this research can concluded that the application of cooperative learning type NHT (Numbered Head Together) can increased study output of the student of class VII MTs Datuk Batu Hampar Bagansiapiapi Academic Year 2015/ 2016.Keyword : Type Numbered Head Together (NHT), IPA study output